WORKING OUT OF THE METHOD OF OUTSOURCING SUBSTANTIATION OF STATE SERVICES IN NONCOMMERCIAL SEGMENT OF PHARMACEUTICAL MARKET - I. A. Dzhuparova (Фармация и фармакология (Пятигорск), 2015)
The article describes the problems of development of an algorithm for state service outsourcing. On the basis of the expert evaluations method we have revealed the priority of factors for evaluation of reasonability of involvement of outsorter-organization with state services rendering.